High-Efficiency Intracavity Continuous-Wave Green-Light Generation by Quasiphase Matching in a Bulk Periodically Poled MgO:LiNbO3 Crystal. (2008) - Chu, Shaowei; Zhang, Ying; Wang, Bin; Bi, Yong
Abstract : 908 mW of green light at 532 nm were generated by intracavity quasiphase matching in a bulk periodically poled MgO:LiNbO 3 (PPMgLN) crystal. A maximum optical-to-optical conversion efficiency of 33.5% was obtained from a 0.5 mm thick, 10 mm long, and 5 mol% MgO:LiNbO 3 crystal with an end-pump power of 2.7 W at 808 nm. The temperature bandwidth between the intracavity and single-pass frequency doubling was found to be different for the PPMgLN. Reliability and stability of the green laser were evaluated. It was found that for continuous operation of 100 hours, the output stability was better than 97.5% and no optical damage was observed.